EFFECTIVENESS OF SCRAPBOOK IN IMPROVING STUDENTS’ DESCRIPTIVE TEXT ANALYSIS SKILLS AT SMPN 4 NGANJUK - Nadilla Helrinda Putri; Nurhamid (Universitas PGRI Mpu Sindok, 2026)
This research investigates the effectiveness of using scrapbook media to enhance students' analytical skills in reading descriptive textst the research problem is the low ability of students in analyzing descriptive texts due to conventional teaching methods that are less engaging and interactive. The study was carried out among the eighth-grade students of SMP Negeri 4 Nganjuk in class VIII- 6 during the 2024/2025 academic year. Employing a pre-experimental design with a one-group pretest-posttest model, the researcher aimed to determine whether scrapbook-based learning could improve students' abilities to analyze descriptive texts.Data were collected through pretests and posttests consisting of multiple- choice questions that measured students’ skills in identifying factual information, language features, and interpreting meanings in descriptive texts. The results revealed a notable increase in the mean score from 45.31 in the pretest to 85.16 in the posttest. Statistical analysis using the paired sample t-test showed a significance value of 0.000 (p < 0.05), indicating a significant difference between students' performance before and after the treatment.These findings suggest that scrapbook-based learning effectively improves students' analytical abilities in reading descriptive texts. The incorporation of scrapbook media not only made the learning process more engaging but also fostered active participation and creativity among students. Therefore, scrapbook can be recommended as an alternative learning medium to support English language teaching, particularly in enhancing reading comprehension and analysis skills in descriptive texts.